SOSIOLOGI LEMBAGA PENDIDIKAN: DESAIN KELAS RESPONSIF TERHADAP KETIMPANGAN SOSIAL DI SMPN 3 KEDUNGBANTENG - Lies Ning Ujiyanti; Muh. Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze responsive classroom design toward social inequality at SMPN 3 Kedungbanteng from the perspective of sociology of educational institutions. The research employed a qualitative approach with a case study design. Data were collected through participant observation, semi-structured interviews, and documentation involving teachers, students, the principal, and the vice principal of facilities and infrastructure. The findings reveal that monolithic and teacher-centered classroom designs reinforce the reproduction of social inequality within the classroom. Students from lower socioeconomic backgrounds tend to occupy back-row seating areas and receive less teacher attention compared to students from higher socioeconomic groups. This inequality is exacerbated by inadequate classroom infrastructure, including damaged projectors, poor lighting, and limited access to digital learning media. Although the school possesses an Interactive Flat Panel (IFP) facility in the science laboratory, its access remains limited and scheduled, thus failing to ensure equitable learning opportunities. The study also found that seating rotation significantly increased the participation of marginalized students. Therefore, classroom design is not a neutral space but functions as an instrument of both reproduction and transformation of social inequality in education. This study recommends more flexible, inclusive, and socially responsive classroom design policies. Keywords: responsive classroom design, social inequality, sociology of education, classroom management, Interactive Flat Panel